The Cambridge world history of food - F Kiple, Kenneth (Cambridge University, 2013)
"This outstanding work of scholarship explains what we eat and why we eat it. The multidisciplinary articles discuss both individual foods and topics such as food fads, famine, and eating disorders."--"Outstanding Reference Sources," American Libraries, May 2001